MENCEGAH PENISTAAN AGAMA DI INDONESIA DENGAN MELEK LITERASI KERAGAMAN BUDAYA - I Nyoman Yoga Segara (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2018)
This article is the result of a recent review of religious defamation in Indonesia isincreasingly occurring, although this problem is not a new thing that not only happens inIndonesia but also in the world. Mass deployment and demonstrations are usually used to dragoff offenders. It seems that this phenomenon is only approached from the perspective of positivelaw only and ignores the socio-cultural aspects that lie behind it. Especially in Indonesia, theactual blasphemy event did not happen suddenly. What often comes to the surface is a politicalissue but it also involves inability to interpret religious and cultural differences. The situationsometimes becomes complex because of the increasingly massive influence of social media.Analysis of social and cultural sciences shows that the need for multicultural education,awareness of pluralism, and cultural literacy. Internalization of this solution should be a habitthat is trained in social life considering that this nation is rich with religious, ethnic, and linguisticdiversity.